Vanadium Contribution to the Surface Modification of Titanium Silicalite for Conversion of Benzene to Phenol - Mulyatun, Mulyatun; Prasetyoko, Didik (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2011)
Vanadium oxide supported on the surface of titanium silicalite was investigated in benzene hydroxylation to determine its activity as heterogeneous catalyst. Effect of vanadium loading on structure and activity of titanium silicalite was investigated. On the basis of X-ray diffraction and infrared spectroscopy techniques, it was found that the titanium structure was remained on the modified catalyst. The catalytic activity of the modified catalyst was observed to be higher than that of parent catalyst.